2013
DOI: 10.1038/cddis.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

Functional cooperation of miR-125a, miR-125b, and miR-205 in entinostat-induced downregulation of erbB2/erbB3 and apoptosis in breast cancer cells

Abstract: We reported that the class I HDAC inhibitor entinostat induced apoptosis in erbB2-overexpressing breast cancer cells via downregulation of erbB2 and erbB3. Here, we study the molecular mechanism by which entinostat dual-targets erbB2/erbB3. Treatment with entinostat had no effect on erbB2/erbB3 mRNA, suggesting a transcription-independent mechanism. Entinostat decreased endogenous but not exogenous erbB2/erbB3, indicating it did not alter their protein stability. We hypothesized that entinostat might inhibit e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 57 publications
10
84
0
1
Order By: Relevance
“…10,11,13,14 Altered expression and/or recruitment of HDACs have been shown to contribute to dysregulation of specific miRNA (e.g., miR-29, miR-200b, miR-31, miR-125a, miR-125b and miR-205) in human breast and lung cancers. [5][6][7][8] Our data show that treatment with Depsi (class I HDAC inhibitor), SAHA (pan-HDAC inhibitor) or 966 (HDAC3-selective inhibitor) resulted in elevated levels of mature miRNA of the miR-15 and let-7 families. This increase in miRNA expression was selective as not all miRNA assessed were induced by HDACi.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…10,11,13,14 Altered expression and/or recruitment of HDACs have been shown to contribute to dysregulation of specific miRNA (e.g., miR-29, miR-200b, miR-31, miR-125a, miR-125b and miR-205) in human breast and lung cancers. [5][6][7][8] Our data show that treatment with Depsi (class I HDAC inhibitor), SAHA (pan-HDAC inhibitor) or 966 (HDAC3-selective inhibitor) resulted in elevated levels of mature miRNA of the miR-15 and let-7 families. This increase in miRNA expression was selective as not all miRNA assessed were induced by HDACi.…”
Section: Discussionmentioning
confidence: 73%
“…One such mechanism that has been linked to HDAC regulation includes microRNA (miRNA). [5][6][7][8] miRNA comprise a class of noncoding RNA that post-transcriptionally regulate the expression of target mRNA, typically resulting in decreased translation. 9 The potential for miRNA-guided regulation of gene expression is significant, as it is predicted that the majority of all mRNAs are under miRNA control and that a single miRNA can target many mRNA.…”
mentioning
confidence: 99%
“…Wang et al and Lyu et al also demonstrated that the overexpression of HER2 promotes HER3 expression via a mechanism involving miR-125a, miR-125b and miR-205 in vivo. 90,91 Bischoff et al found that miR-148b, miR-149, miR-326, and miR-520a-3p directly reduced HER3 mRNA and protein levels. 85 Yan et al 92 provided insights into the role of the miR-143/145 cluster as a tumor suppressor in breast cancer; that is, they suggested that it inhibits HER3 translation in vivo.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…3). [60][61][62][63] As we describe below, 2 major lines of evidence motivated the current intensified interest in intercepting HER3 in human tumors: First, oncogenic mutant forms have recently been identified in approximately 10% of solid tumors and second, several studies indicated that HER3 plays pivotal roles in several compensatory processes that underlay emergence of resistance to certain cancer drugs. 64,65 …”
Section: Targeted Cancer Therapy Directed At the Egfr (Her/ Erbb) Familymentioning
confidence: 99%
“…Entinostat downregulates HER3 and HER2 via induction of specific microRNAs (miR-125a, miR125b, and miR205) in HER2-overexpressing breast cancer cells. 63 Likewise, several antisense oligonucleotides or microRNAs seems able to downregulate HER3, such as a locked nucleic acid (LNA)-based HER3 antisense oligonucleotide called EZN-3920, 95 which improves the anti-tumor activity of TKIs, and miR-450b-3p, which inhibits proliferation of breast cancer cells. 60 Targeting mRNAs with LNA EZN-3920 provided promising preclinical strategy but further development remains a challenge.…”
Section: Others Indirect Strategiesmentioning
confidence: 99%